BOOK REVIEW: Halal Logistics and Supply Chain Management in Southeast Asia - Priantina, Anita (Jurnal Sosioteknologi, 2024)
Halal logistics and halal supply chain management play essential role in the halal assurance system. Southeast Asia consist of some muslim majority populated countries, and countries with significant number of muslim consumers. The emerging concern towards halal logistics is a certainty after the rising concern worldwide towards halal industry and halal certification system. Southeast Asia is also a home of a country which has announced the mandatory halal certification. The discussion which spans from theoretical perspectives into empirical implementation of policies related to halal logistics in this region may give insight into how halal assurance should be prepared and executed. Articles in this book written with similar conclusions stating that halal is not merely conceptual religious obligations, but also needs technical implementation which will need comphrehensive frameworks. These frameworks consists of inter-related elements which are essential for the optimum system operation. The studies also elaborate opportunities and room for improvements in this halal logistics sector, in order to maintain the optimum total halal assurance implementation.